Inhibition of Extracellular Cathepsin D Reduces Hepatic Lipid Accumulation and Leads to Mild Changes in Inflammationin NASH Mice - Yadati, Tulasi; Houben, Tom; Bitorina, Albert; Oligschlaeger, Yvonne; Gijbels, Marion J.; Mohren, Ronny; Lütjohann, Dieter; Khurana, Princy; Goyal, Sandeep; Kulkarni, Aditya; Theys, Jan; Cillero-Pastor, Berta; et al. (Frontiers in Immunology, 2021)
Background & aims: The lysosomal enzyme, cathepsin D (CTSD) has been implicated in the pathogenesis of non-alcoholic steatohepatitis (NASH), a disease characterised by hepatic steatosis and inflammation. We have previously demonstrated that specific inhibition of the extracellular CTSD leads to improved metabolic features in Sprague-Dawley rats with steatosis. However, the individual roles of extracellular and intracellular CTSD in NASH are not yet known. In the current study, we evaluated the underlying mechanisms of extracellular and intracellular CTSD fractions in NASH-related metabolic inflammation using specific small-molecule inhibitors. Methods: Low-density lipoprotein receptor knock out (Ldlr-/-) mice were fed a high-fat, high cholesterol (HFC) diet for ten weeks to induce NASH. Further, to investigate the effects of CTSD inhibition, mice were injected either with an intracellular (GA-12) or extracellular (CTD-002) CTSD inhibitor or vehicle control at doses of 50 mg/kg body weight subcutaneously once in two days for ten weeks. Results: Ldlr-/- mice treated with extracellular CTSD inhibitor showed reduced hepatic lipid accumulation and an associated increase in faecal bile acid levels as compared to intracellular CTSD inhibitor-treated mice. Furthermore, in contrast to intracellular CTSD inhibition, extracellular CTSD inhibition switched the systemic immune status of the mice to an anti-inflammatory profile. In line, label-free mass spectrometry-based proteomics revealed that extra- and intracellular CTSD fractions modulate proteins belonging to distinct metabolic pathways. Conclusion: We have provided clinically translatable evidence that extracellular CTSD inhibition shows beneficial metabolic and systemic inflammatory effects which are distinct from intracellular CTSD inhibition. Considering that intracellular CTSD inhibition is involved in essential physiological processes, specific inhibitors capable of blocking extracellular CTSD activity, can be promising and safe NASH drugs.